Smarter and Greener: How Does Intelligent Manufacturing Empower Enterprises’ Green Innovation? - Chen, Shuying; Gao, Da; Tan, Linfang (Sustainability, 2025)
Intelligent manufacturing is the inevitable path for China to achieve its strategy of becoming a manufacturing power. Exploring how intelligent manufacturing policies can promote green innovation, which refers to promoting innovative technologies aimed at improving resource utilization efficiency, is of great significance for promoting the green transformation of enterprises. Based on the data of A-share listed enterprises from 2010 to 2023, this study regards the intelligent manufacturing demonstration project pilot as a quasi-natural experiment and explores its policy spillover effects and mechanism. The research findings indicate that the intelligent manufacturing policy can greatly improve firms’ green innovation, and non-state-owned and non-high-pollution enterprises are more sensitive to intelligent manufacturing policies. It has a significant spatial spillover effect in both the district and industry dimensions. In addition, the mechanism analysis indicates that alleviating enterprises’ financing constraints and environmental uncertainty are important ways to promote enterprises’ green innovation. This study empirically designs to fill the theoretical gap in the association between intelligent manufacturing policies and green innovation in the body of knowledge, and innovatively verifies the spatial spillover effect of intelligent manufacturing policies from both the district and industry dimensions. At the practical level, its conclusion provides an operational decision-making toolbox for multiple entities such as the government, enterprises, and financial institutions to jointly promote green transformation.